2016
DOI: 10.1103/physrevd.93.103513
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational baryogenesis after anisotropic inflation

Abstract: The gravitational baryogensis may not generate a sufficient baryon asymmetry in the standard thermal history of the Universe when we take into account the gravitino problem. Hence it has been suggested that anisotropy of the Universe can enhance the generation of the baryon asymmetry through the increase of the time change of the Ricci scalar curvature. We study the gravitational baryogenesis in the presence of anisotropy, which is produced at the end of an anisotropic inflation. Although we confirm that the g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…The scalar-vector coupling term has been shown to be a source of stable anisotropy. Consequently, many cosmological aspects of this model have been investigated extensively [67][68][69][70][71][72][73][74][75][76]. Along this line of research, the validity of the cosmic no-hair conjecture has been investigated systematically in some non-canonical extensions of the KSW model with the canonical scalar field model is replaced by non-canonical models.…”
Section: Introductionmentioning
confidence: 99%
“…The scalar-vector coupling term has been shown to be a source of stable anisotropy. Consequently, many cosmological aspects of this model have been investigated extensively [67][68][69][70][71][72][73][74][75][76]. Along this line of research, the validity of the cosmic no-hair conjecture has been investigated systematically in some non-canonical extensions of the KSW model with the canonical scalar field model is replaced by non-canonical models.…”
Section: Introductionmentioning
confidence: 99%
“…[32,33] that there exists an anisotropic power-law inflationary attractor yielding constant expansion anisotropy σ 2 /H 2 , in the presence of exponential scalar potential and such a coupling of the exponential form, which often appears in string theory and supergravity [34,35]. These studies are followed by many cosmological predictions [25,[36][37][38][39][40][41] and further extension to various models [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%
“…Davoudiasl et al [9] have shown that the gravitational interaction between the baryon-number current and the derivative of Ricci scalar curvature dynamically breaks the CPT symmetry in an expanding Universe. Since the proposal of Davoudiasl et al, the gravitational baryogenesis has gained a lot of popularity and many generalizations of the original mechanism have been proposed [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%